What about virtual creative knowledge environments? Definition and modelling through case-based reasoning. (2017) - Sartori, Fabio
Support for virtual creative knowledge environments is a new and challenging research topic in knowledge management research field. Starting from the definitions of creative thinking, creative space and creative knowledge environments, this paper reflects on how such concepts can be properly modelled. The adoption of the case-based reasoning paradigm has allowed to build up a conceptual and computational framework able to promote them from both the theoretical and practical points of view.